1997
DOI: 10.1046/j.1365-2036.1997.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical economics review: irritable bowel syndrome

Abstract: The ubiquitous nature of irritable bowel syndrome (IBS), coupled with a lack of good treatment options, has created the impression that the condition must represent a large drain on health‐care resources. The literature certainly appears to support this view but is largely based on patients seen in referral centres (10–15%) and it may not be appropriate to extrapolate these data to the IBS population as a whole (85–90%).In addition to reviewing such literature that exists on the economics of IBS, this paper co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 26 publications
(29 reference statements)
0
74
0
4
Order By: Relevance
“…A study by Wells et al (14) estimated that, in 1995, the direct costs associated with this condition over a one-year period in the United Kingdom averaged £45.6 million. The total expenditures were based on the following costs: physician visits (£13.1 million), prescribed medications (£12.5 million), hospital outpatient visits (£16.6 million) and inpatient admissions (£3.4 million).…”
Section: Economic Impact Of Ibsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Wells et al (14) estimated that, in 1995, the direct costs associated with this condition over a one-year period in the United Kingdom averaged £45.6 million. The total expenditures were based on the following costs: physician visits (£13.1 million), prescribed medications (£12.5 million), hospital outpatient visits (£16.6 million) and inpatient admissions (£3.4 million).…”
Section: Economic Impact Of Ibsmentioning
confidence: 99%
“…Although IBS is not life-threatening, patients report limited and constrained lives that have been modified to cope with their disease. In a study conducted by Wells et al (14), the qualities of lives of patients with different medical afflictions were compared and examined. Mean scores on the Short Form-36 IBS-specific quality of life (IBSQOL) questionnaire for patients with diabetes, acute myocardial infarction, hypertension and clinical depression were compared with the IBS mean for a tertiary care group and with the national norms for nonpatients.…”
Section: Economic Impact Of Ibsmentioning
confidence: 99%
“…American studies have reported how costly IBS is both in terms of healthcare use and lost productivity, whereas assessments in the UK have been more cautious. [58][59][60][61][62][63][64][65][66] There has been surprisingly little assessment of the opportunity costs of IBS. In addition, although various new pharmaceutical preparations have been trialled there has been little published economic analysis of these treatments.…”
Section: Economic Analysesmentioning
confidence: 99%
“…Unfortunately, the understanding of the pathogenesis and pathophysiology of these disorders is limited and there are few effective treatment options [Spiller et al 2007]. Moreover, healthcare consumption in this group of patients is high, and since IBS is a very common, chronic disorder with severe symptoms, the economic consequences of the disorder are profound [Wells et al 1997].…”
Section: Introductionmentioning
confidence: 99%